2018
DOI: 10.20885/jaai.vol22.iss2.art1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of transfer pricing decisions in Indonesia manufacturing companies

Abstract: This research aims to investigate tax expenses, tunneling, and bonus on transfer pricing decisions in Indonesia. The practice of transfer pricing as one form of tax avoidance may threaten state revenues. This research is quantitative research with multiple linear regression models with panel data. The samples used in this research are manufacturing companies listed on the Indonesia Stock Exchange (IDX). The type of data used in this study is secondary data in the form of financial statements of companies liste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 11 publications
2
35
1
14
Order By: Relevance
“…Moreover, based on Indonesian manufacturing firms' characteristics, an effective mechanism for corporate governance with most of commissioners meeting requirements and with overstating profits of bonus mechanism is still very rare. This study's findings support research by (Susanti & Firmansyah 2018), showing that the bonus mechanism does not affect transfer pricing. If companies shift profits to related enterprises, the effects decrease bonuses and deteriorate the company's reputation through an opportunistic act such as aggressive tax avoidance by transfer pricing.…”
Section: The Effect Of Bonus Mechanism On Transfer Pricing Decisionssupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, based on Indonesian manufacturing firms' characteristics, an effective mechanism for corporate governance with most of commissioners meeting requirements and with overstating profits of bonus mechanism is still very rare. This study's findings support research by (Susanti & Firmansyah 2018), showing that the bonus mechanism does not affect transfer pricing. If companies shift profits to related enterprises, the effects decrease bonuses and deteriorate the company's reputation through an opportunistic act such as aggressive tax avoidance by transfer pricing.…”
Section: The Effect Of Bonus Mechanism On Transfer Pricing Decisionssupporting
confidence: 88%
“…Besides, research from Azzura & Pratama (2019) and Nuradila & Wibowo (2018) has shown that tunneling incentives have a major impact on Indonesia's transfer pricing. While the business becomes a public enterprise, the group's influence is still significant (Susanti & Firmansyah, 2018). Because in Indonesia, firms have consolidated shareholding and broad company influence tunneling for transfer pricing, can be easily enforced.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon said by Mispiyanti (2015) can cause the fiscal authority in this case the Directorate General of Taxes (Direktorat Jendral Pajak) assumes that the purpose of transfer pricing is to avoid taxes. Susanti & Firmansyah (2018) also said that transfer pricing is often used in the case of shifting profits from companies in countries with higher tax rates to affiliated companies in countries with lower tax rates, so it can be concluded that from the government's view of transfer pricing it is believed will result in a reduced potential for tax revenue from a country. Regulations regarding transfer pricing have been made by the fiscal authority very comprehensively, but in reality, cases of tax violations have been found through a transfer pricing scheme.…”
Section: Conducted At the Shanghai Stockmentioning
confidence: 99%
“…Conglomerate companies are owned by majority shareholders who also own shares in other related companies, this causes tunneling activities to provide benefit to majority shareholders(Susanti & Firmansyah, 2018) Mutamimah (2009). states that tunneling incentive is a behavior of majority shareholders who transfer company assets and profits for their own benefit, but minority shareholders also bear the costs that used by majority shareholder to transferring assets and profits.Chan et al (2016) in his research stated that tunneling was caused by the majority ownership of controlling shareholders and inadequate corporate governance.…”
mentioning
confidence: 99%